The semiotic of Bangkai-Bangkaian: A special space for the spirit - Halina Sendera Mohd. Yakin; Andreas Totu (2015)
The main purpose of this paper is to ethnographically describe the ritual of death among the West Coast Bajau in Sabah especially on the matters related to the preparation of bangkai-bangkaian after a funeral. This cultural artifact is perceived as a resting place or ‘special space’ for a spirit which is believed will visit his or her family members during special feast and occasion known as bejogo, mangan bangi and malam tujuh. Apart from that, bangkai-bangkaian also symbolizes the values of love, care and respect for the dead. Symbolically, the act of preparing bangkai-bangkaian also reflects the world-view of the Bajau. The discussion also covers the concept of spirit’s space among other ethnic groups in Sabah. The data were gathered through interviews and participant observations carried out in Kampung Kota Belud, Sabah, Malaysia. The qualitative description were analyzed and elucidated based on semiotic and non-verbal communication perspectives.